COVID-19 Emergency: Boosting Digitalization and a Missed Opportunity for Acquiring Digital Literacy in the Old Population - Carlo, Simone; Nanetti, Sara (Socialinė teorija, empirija, politika ir praktika, 2024)
The COVID-19 crisis has accelerated the adoption of digital content and services, particularly in Italy, a country historically slower in embracing communication technologies (European Commission, 2023). Mobility restrictions have hastened the digitalization of daily life, including communication, entertainment, and utility services (Auditel & Censis, 2022). Older individuals, traditionally less digitally proficient, have faced challenges adapting to this rapid digitalization (Rolandi et al., 2020, NIHR, 2022). However, early evidence suggests that this digital acceleration may not be sufficient to bridge the digital divide, especially among older populations (Litchfield et al., 2021, Colombo et al., 2023). This paper explores the changes occurring in the relationship between older people and new technologies based on data provided by longitudinal qualitative research, which involved a panel of 40 over-65 residents in the Lodigiano region, the first red zone – affected by the pandemic and its restrictions – in Europe. This contribution aims to highlight how active seniors have experienced a transformation in their approach to technology from the onset of the pandemic (2020) to the present day. The interviews were transcribed verbatim and then imported into the NVivo application for content analysis. Grounded Theory (Glaser & Strauss, 1967) was utilized, involving several stages. The analysis also aimed to formulate ideal types for interpreting the diverse approaches to digital adoption among the older population. From the present study, it emerged that the rapid process of digitalization during the COVID-19 pandemic has not effectively bridged the digital divide, but rather widened it. The swift digitalization of public services highlights the challenges in ensuring inclusivity, especially for older individuals. While digitalization can benefit those with support networks, it further marginalizes isolated seniors. Policy-makers need to consider existing caregiver networks to promote digital inclusion among older individuals.
Keywords: Ageing; ICTs; Covid-19; Digital Divide; qualitative methodology